Development and Validation of an Leo-Friendly and Low-Cost Method for the Quantification of Cefepime Hydrochloride in Powder for Injectable Solution Using Infrared (IR) Spectroscopy - Rodrigues, Danilo F. [UNESP]; Salgado, Herida R. N. [UNESP] (Bentham Science Publ Ltd, 2020)
Background: A simple, eco-friendly and low-cost Infrared (IR) method was developed and validated for the analysis of Cefepime. Hydrochloride (CEF) in injectable formulation. Different from some other methods, which employ organic solvents in the analyses, this technique does not use these types of solvents, removing large impacts on the environment and risks to operators. Objective: This study aimed at developing and validating a green analytical method using IR spectroscopy for the determination of CEF in pharmaceutical preparations. Methods: The method was validated according to guidelines and the quantification of CEF was performed in the spectral region absorbed at 1815-1745 cm(-1) (stretching of the carbonyl group of beta-lactam ring). Results: The validated method showed to be linear (r = 0.9999) in the range of 0.2 to 0.6 mg/pellet of potassium bromide, as well as for the parameters of selectivity, precision, accuracy, robustness and Limits of Detection (LOD) and Quantification (LOQ), being able to quantify the CEF in pharmaceutical preparations. The CEF content obtained by the IR method was 103.86%. Conclusion: Thus, the method developed may be an alternative in the quality control of CEF sample in lyophilized powder for injectable solution, as it presented important characteristics in the determination of the pharmaceutical products, with low analysis time and a decrease in the generation of toxic wastes to the environment.
Keywords: Cefepime hydrochloride; green chemistry; pharmaceutical analysis; quality control; spectroscopy; validation